2018
DOI: 10.2174/1570180815666180502120042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Evaluation and In silico Studies of Novel 2,4- disubstituted-1,3-thiazole Derivatives

Abstract: Background: 2,4-disubstituted-1,3-thiazole derivatives (2a–j), (3a–f) and (4a–f) were synthesized, characterized and screened for their potential as antimicrobial agents. In the preliminary screening against a panel of bacterial strains, nine compounds showed moderate to potent antibacterial activity (IC50 = 13.7-90.8 μg/ml). </P><P> Methods: In the antifungal screening, compound (4c) displayed potent antifungal activity (IC50 = 26.5 &#181;g/ml) against Candida tropicalis comparable to the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, due to handling problems associated with α‐bromoketones such as low melting, toxicity and lachrymosity, the use of α,α‐dibromoketones in modified HTS is appreciable. Synthesis of new derivatives of thiazoles is encouraged as (a) the wonder motif is endowed with remarkable biological activities particularly antimicrobial and antitumor, (b) there is continuous need for new antibiotics because the disease causing microbes become resistant to existing antibiotic arsenal . Combining thiazole with another five‐membered diheteroatomic N‐containing heterocycle, the pyrazole core in a single hybrid structure are expected to impart distinct and interesting structural and biological characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to handling problems associated with α‐bromoketones such as low melting, toxicity and lachrymosity, the use of α,α‐dibromoketones in modified HTS is appreciable. Synthesis of new derivatives of thiazoles is encouraged as (a) the wonder motif is endowed with remarkable biological activities particularly antimicrobial and antitumor, (b) there is continuous need for new antibiotics because the disease causing microbes become resistant to existing antibiotic arsenal . Combining thiazole with another five‐membered diheteroatomic N‐containing heterocycle, the pyrazole core in a single hybrid structure are expected to impart distinct and interesting structural and biological characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…In our continuous efforts to design biologically active heterocycles, [12][13][14][15][16][17] we hypothesized albaconazole as a model for preparation of 1,2,3-triazole derivatives of quinazolin-4(3H)-one (5a-q and 6a-q) and studied their antifungal properties. Further, single crystal X-ray study of compounds 2 and 5c has been reported.…”
Section: Introductionmentioning
confidence: 99%